2017
DOI: 10.1016/j.carbon.2016.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and gas-surface interaction studies of a 3D carbon/carbon composite in atmospheric entry plasma

Abstract: 3D Carbon-fiber reinforced carbon composites (3D C f /C) are widely used as thermostructural protections in various applications. Among them, thermal protection systems for atmospheric re-entry encounter one of the most aggressive environments, where 3D C f /C are exposed to strong ablation. Because flight tests are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…One important aspect of oxidation relates to the evolution of the carbon surface topology, the phenomenon generically called "pitting". [25][26][27][28] Past experimental studies have found that in certain conditions, oxidation does not occur uniformly but takes the form of pits or crater-like cavities, randomly scattered across the otherwise smooth carbon surface. [29][30][31][32][33] These pits initiate at atomic vacancies, defects, or basal plane carbon atoms, 33,34 eventually reaching the scale of the diameter of the fibers.…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect of oxidation relates to the evolution of the carbon surface topology, the phenomenon generically called "pitting". [25][26][27][28] Past experimental studies have found that in certain conditions, oxidation does not occur uniformly but takes the form of pits or crater-like cavities, randomly scattered across the otherwise smooth carbon surface. [29][30][31][32][33] These pits initiate at atomic vacancies, defects, or basal plane carbon atoms, 33,34 eventually reaching the scale of the diameter of the fibers.…”
Section: Introductionmentioning
confidence: 99%
“…10 It is widely agreed that the combination of 3D printing and CF is able to produce complex structure and high-performance products with high efficiency. 11,12 Hence, the integration can be regarded as the powerful driving force for the development of 3D printing and CF applications.…”
Section: Introductionmentioning
confidence: 99%
“…Baxter et al [8] studied the effect of chemical vapor infiltration (CVI) on the corrosion and thermal conduction of porous C/C composite, and found that both radiative heat transfer and the heat transfer path in pores played important roles in the parallel path thermal conduction. The ablation behavior of C/C composite was also studied by other researchers [9,10]. As for high-thermal-conductive C/C composite, carbon fiber (CF) is not only the reinforcement of the composite, but also the carrier of heat [11].…”
Section: Introductionmentioning
confidence: 99%